Pengembangan dan Pengenalan Kaos “Ndlodok” Endymion Screen Printing Melalui Promosi - Kasnowo Kasnowo (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
The creative industry is an industry that focuses on the creation and exploitation of intellectually owned works, one of which is fashion design, including t-shirts. The current condition of society, both individuals and groups, are now starting to build their brands with the innovation and creativity they build, including Ndlodok T-shirts. This community service is the second stage, namely to introduce ndlodok t-shirts to the community. The initial offer of the "Ndlodok" T-shirt was to formulate a library-based "Ndlodok" T-shirt with characteristics of the Mojokerto dialect with the hope of opening up a new market. Apart from that, the product would become a souvenir that consumers were looking for because it had become a characteristic of Mojokerto UMKM. In facing the rigors of UMKM businesses which are increasingly competitive, "Ndlodok" T-shirt products do not experience problems in the middle of their journey, at this early stage it is necessary to introduce them as a reference for "Ndlodok" T-shirts in carrying out promotional activities.